Earning Management on Market Performance: The Empirical Study on Dividend and Working Capital - Siladjaja, Muljanto (Universitas Pendidikan Indonesia, 2019)
Abstract. This research is to develop the integrated modeling for illustrating the influence of accruals against on the market value of firm performance through the corporate event policy, both the policy of dividend payout and working capital, so this causal relationship involves the quality of accruals. On the side, this research tests the capability skill of investors to detect earnings management by the period of publication, when the issue was released out formally and informally. This research proves the empirical testing, earnings management that are commonly used to sending out the message or signaling to the market about firm performance, this fundamental aim is to match the different perceptions. This research used the statistical models by developing the ANOVA analysis, the path model analysis, and multivariate regression, where our explanatory causal research has two stages of the data analysis. Primarily, we used testing the influence of discretionary accruals by path analysis and multivariate regression. By getting rid of the available error or bias, the object of this research was all the listed company period 2001-2016, where it has the purposive sampling. This research used the Amos and SPSS at the significant level at 5%. Finding, the critical finding that all public firms have a systematic method for earnings management, we distinguished the discretionary accruals, when it had high and low accruals, it is measured by the percentage of the total accruals. The discretionary accruals have a negative influence on the market value significantly, both indirect and direct impact. The indirect could be done by a positive relationship with a dividend and a negative relationship with working capital. The other finding is the impact on the quality of accruals when estimating the risk of the firm and the usefulness of financial reporting. This research tries to prove the dividend policy, based on earnings management, and working capital had been a sensitive indicator for investors. Research limitation, this research based on the fundamental analysis, then developed into accruals testing with Kothari Model. When we used the financial indicators, it so brings so many limitations, like the lag period and time horizon. By ignoring the error in time horizon accruals in the long run, this research testing between the accruals and corporate events policy. Practical Implication, this research has pointed out the financial reporting still be the most valuable document and the high usefulness in taking an investment decision. The investors have the capability to detect earnings management and capable too of making a judgment when the high accruals could be found. When a firm released out the financial reporting, it is just like game theory. When financial reporting have high accruals, so this management used the conservative method in reducing out the risk, as we are commonly known as the quality of accruals. Originality/value, The researchers have developed out a mutual relationship with corporate earnings management policy and market value by proposing the concept of the market value of accruals, high payout dividend yield and quality of accruals. By re-shaping the new paradigms of dividend payout, and increasing capability skills of investors, we develop the matrix of game theory models in illustrating investor and management behavior; include the pattering of the flexibility of the accounting method.Â Keywords.Â discretionary accruals; working capital; dividend payout; quality of accruals; the cost of capital.